Cannabinoids on the Brain - Andrew J. Irving; Mark G. Rae; Angela A. Coutts (The Scientific World Journal)
Cannabis has a long history of consumption both for recreational and medicinal uses. Recently there have been significant advances in our understanding of how cannabis and related compounds (cannabinoids) affect the brain and this review addresses the current state of knowledge of these effects. Cannabinoids act primarily via two types of receptor, CB1 and CB2, with CB1 receptors mediating most of the central actions of cannabinoids. The presence of a new type of brain cannabinoid receptor is also indicated. Important advances have been made in our understanding of cannabinoid receptor signaling pathways, their modulation of synaptic transmission and plasticity, the cellular targets of cannabinoids in different central nervous system (CNS) regions and, in particular, the role of the endogenous brain cannabinoid (endocannabinoid) system. Cannabinoids have widespread actions in the brain: in the hippocampus they influence learning and memory; in the basal ganglia they modulate locomotor activity and reward pathways; in the hypothalamus they have a role in the control of appetite. Cannabinoids may also be protective against neurodegeneration and brain damage and exhibit anticonvulsant activity. Some of the analgesic effects of cannabinoids also appear to involve sites within the brain. These advances in our understanding of the actions of cannabinoids and the brain endocannabinoid system have led to important new insights into neuronal function which are likely to result in the development of new therapeutic strategies for the treatment of a number of key CNS disorders.